Weak solutions to discrete nonlinear two-point boundary-value problems of Kirchhoff type - Blaise Kone (Electronic Journal of Differential Equations, 2015)
In this article, we prove the existence of weak solutions to a family of discrete boundary-value problems whose right-hand side belongs to a discrete Hilbert space. As an extension, we prove the existence of weak solutions for problems whose right-hand side depends on the solution.